Evaluation of a systematic postal screening and treatment service for genital Chlamydia trachomatis, with remote clinic access via the internet: a cross-sectional study, East of England. Issue 5 (28th February 2012) - Bracebridge, Samantha; Bachmann, Max Oscar; Ramkhelawon, Krishna; Woolnough, Alison
Abstract : Objective: England's National Chlamydia Screening Programme provides opportunistic testing for all 15–24-year-olds in healthcare and non-healthcare settings. The authors undertook an evaluation of a population service-based postal chlamydia screening and treatment service, with registration and access to the service via the internet, in order to target screening interventions more effectively in future. Methods: Individuals aged between 18 and 24 years, within the North East Essex Primary Care Trust, were identified for chlamydia screening by the service between 1 December 2008 and 31 January 2009. Associations between test uptake and positivity, and individuals' personal characteristics, were examined. The efficacy of partner notification was estimated, and the costs of screening were compared with the national average. Results: Uptake of chlamydia screening was 11.5%, with lower response rates among men, individuals older than 20 years and those living in more deprived areas. The chlamydia positivity was 4.4% and higher in those reporting multiple sexual partners, individuals older than 20 years and those living in more deprived areas. The proportion of partners notified per index case was 0.17. The service contributed to 3431 of the overall 11 209 annual chlamydia screens of the Primary Care Trust in 2008–2009, at a cost of £78 per screening test completed and £1764 per case detected. Conclusions: Our evaluation shows that this service model can contribute substantially to the overall coverage of chlamydia screening tests. However, the costs of service provision per case detected and treated, using this model, were high compared to the National Chlamydia Screening Programme.